Distribution Temperature, Salinity And Dissolved Oxygen In Waters Kema, North Sulawesi - Simon I Patty (Jurnal Ilmiah PLATAX, 2013)
ABSTRACT Distribution Temperature, Salinity and Dissolved Oxygen in Kema Waters, North Sulawesi. Distribution of temperature, salinity and dissolved oxygen in the water is very influential on the various aspects of the other parameters, such as chemical reactions and biological processes. Research on the conditions of temperature, salinity and dissolved oxygen in the Kema waters, North Sulawesi in April and May 2010. The results showed that temperature ranges from 28.2 to 32.5°C with an average of (30.1 ± 1.11°C), salinity between 28.0 to 33.0o/oo with an average of (31.7 ± 1.36o/oo) and dissolved oxygen between 3.46 to 6.25 ppm with an average of (4.73 ± 0.76 ppm). Distribution of values ​​of temperature, salinity and dissolved oxygen levels vary. Variations in temperature, salinity and dissolved oxygen in these waters was affercted by external factors including weather, wind and currents. Conditions of temperature, salinity and dissolved oxygen in this waters were still relatively normal and preferable for marine life. Keywords : temperature, salinity, dissolved oxygen, Kema, North Sulawesi   ABSTRAK Distribusi suhu, salinitas dan oksigen terlarut di suatu perairan sangat berpengaruh pada berbagai aspek parameter lain, seperti reaksi kimia dan proses biologi. Penelitian mengenai kondisi suhu, salinitas dan oksigen terlarut di perairan Kema, Sulawesi Utara dilakukan pada bulan April dan Mei 2010. Hasilnya menunjukkan suhu berkisar antara 28,2 - 32,5oC dengan  rata-rata (30,1±1,11oC), salinitas antara 28,0-33,0o/oo dengan rata-rata (31,7±1,36o/oo) dan oksigen terlarut antara 3,46-6,25 ppm dengan rata-rata (4,73±0,76 ppm). Sebaran nilai suhu, salinitas dan kadar oksigen terlarut cukup bervariasi. Bervariasinya suhu, salinitas dan oksigen terlarut di perairan ini dipengruhi oleh fakktor eksternal antara lain cuaca, angin dan arus. Kondisi suhu, salinitas dan oksigen terlaut perairan ini masih tergolong normal dan baik untuk kehidupan biota laut. Kata kunci : suhu, salinitas, oksigen terlarut, Kema, Sulawesi Utara